Pengaruh Iklan Live Streaming Shopee terhadap Keputusan Pembelian Dimoderasi oleh Sikap - Syahedah Soeci Elfera; Dadang Sugiana; Iriana Bakti (Jurnal Riset Komunikasi (JURKOM), 2024)
Live streaming is a new phenomenon and is an effective digital marketing strategy to attract consumer attention and encourage purchasing decisions. This article aims to analyze the influence of cognitive responses to e-commerce live-streaming advertisements on purchasing decisions. The research was conducted using quantitative methods. Data was collected through a survey of 96 respondents who had made purchases on Shopee e-commerce and watched live streaming. Data testing uses Path Analysis with Structural Equation Modeling (SEM) analysis techniques through the Partial Least Square (PLS) process. The research results show that cognitive responses to live-streaming advertisements have a positive influence on purchasing decisions through attitude as a mediating variable with a value of 0.564 or 56%. This is in line with the assumptions of cognitive response theory, namely how consumers process information from advertising and how this cognitive response influences their attitudes and purchasing decisions. Consumer cognitive responses are obtained through consumer thoughts about products, consumer thoughts on information sources and consumer thoughts on advertising. These factors will lead to the formation of attitudes, both attitudes towards the brand and attitudes towards advertising, with the final stage being the purchasing decision. The findings in this article provide a practical impression for e-commerce business people to focus on improving the quality of content and interactions between business people when live streaming is taking place.